2016
DOI: 10.1016/j.apsusc.2016.06.088
|View full text |Cite
|
Sign up to set email alerts
|

Superhydrophilicity of a nanofiber-covered aluminum surface fabricated via pyrophosphoric acid anodizing

Abstract: Superhydrophilicity of a nanofiber-covered aluminum surface was investigated. Anodic alumina nanofibers were formed via pyrophosphoric acid anodizing. Nanofiber-covered aluminum surface displays fast and stable superhydrophilicity. The quick-drying and snow-sliding behaviors were demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…The contact angle of the droplet formed on the rough surface can be described by Wenzel’s equation as [56] cos θ W = R cos θ where R corresponds to the specific surface area, and θ W and θ are the contact angles obtained on the rough surface and the flat surface, respectively. The anodic alumina nanofibers formed by pyrophosphoric acid anodizing consists of pure aluminum oxide without any electrolyte anion, and anodic aluminum oxide exhibits hydrophilicity due to the presence of the surface-bound hydroxyl groups [51]. Therefore, Wenzel’s equation indicates that the contact angle decreases with increasing specific surface area on such a hydrophilic surface.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The contact angle of the droplet formed on the rough surface can be described by Wenzel’s equation as [56] cos θ W = R cos θ where R corresponds to the specific surface area, and θ W and θ are the contact angles obtained on the rough surface and the flat surface, respectively. The anodic alumina nanofibers formed by pyrophosphoric acid anodizing consists of pure aluminum oxide without any electrolyte anion, and anodic aluminum oxide exhibits hydrophilicity due to the presence of the surface-bound hydroxyl groups [51]. Therefore, Wenzel’s equation indicates that the contact angle decreases with increasing specific surface area on such a hydrophilic surface.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the fabrication of highly slippery and sticky superhydrophobic aluminum surfaces is easily achieved via the nanostructure control of alumina nanofibers [50]. On the other hand, the nanofiber-covered aluminum surface without SAM modification exhibits superhydrophilic behavior [51,52,53]. The contact angle measured on the superhydrophilic aluminum surface greatly changed with the anodizing time.…”
Section: Introductionmentioning
confidence: 99%
“…3− is concentrated in the intermediate part of the outer wall. As an interesting example, anodization in pyropohospohoric acid should be mentioned, which leads to the formation of honeycomb oxide with nanofibers [99,100]. The electron energy loss spectroscopy (EELS) revealed that phosphorus was incorporated into the barrier layer; however, the nanofibers were composed of relatively pure alumina, equivalent to the previously reported "interstitial rods".…”
Section: Mechanism Of Anions Incorporation: Duplex and Triplex Structurementioning
confidence: 88%
“…A nanober-covered aluminum surface exhibits superhydrophilic properties with a water contact angle (WCA) of less than 10 observed within 0.1 seconds aer placement of the water drop. 29,30 Rapid drying and snow-sliding behaviors were observed on these aluminum surfaces covered with alumina nanobers. Conversely, the WCA drastically changes to show superhydrophobic behavior and is over 150 when the surface of the alumina nanobers is modied with a self-assembled monolayer (SAM).…”
Section: Introductionmentioning
confidence: 96%